작목별 농작물재해보험의 확대 가능성 분석 - 최경환 (한국농촌경제연구원, 2003)
An Analysis of the Possibility of Adopting Crop Insurance by Crop The purpose of this study is to analyse the feasibility of adopting crop insurance by crop. The major research methods include the review of related literature, the survey about farmers' attitudes towards agricultural risks and crop insurance for selected crops, and the collection of related data. Descriptive statistics were used to organize and summarize the data surveyed. Crop insurance program has been implemented for six crops (apple, pear, grape, peach, persimmon, and orange). It is necessary to gradually expand the crop insurance scheme to other possible crops. In this study, the criteria for feasibility consideration encompass the number of cultivating farmers, the size of cultivated area, and the production amount per farm household by crop. The most possible crop for adopting crop insurance based on the above criteria is paddy rice, to which most farm households' income are related. Also there are relatively sufficient data and knowhows for the rice that have been accumulated for several years. The other possible crops are horticulture and floriculture. Although the share of these crops are small in terms of the number of farmers and the size of cultivated area, they are very important in terms of farm household income. However, the facilities for horticulture and floriculture are more important than yields in adopting crop insurance. In reality, in order to implement crop insurance for paddy rice, vegetable and flower, sufficient preparation is needed before adopting crop insurance. Researcher: Choi Kyeong-Hwan E-mail Address: kyeong@krei.re.kr
Keywords: 농작물재해보험 농업경영 보험작물